2007
DOI: 10.1098/rsta.2007.2168
|View full text |Cite
|
Sign up to set email alerts
|

Using surface force apparatus, diffusion and velocimetry to measure slip lengths

Abstract: Determining the slip lengths for liquids flowing close to smooth walls is challenging. The reason lies in the fact that the scales that must be addressed range between a few and hundreds of nanometres. Several techniques have been used over the last few years. Here, we consider three of them based on surface force apparatus, diffusion and velocimetry, respectively. The descriptions offered here incorporate recent instrumental progress made in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…In this case, the fluid's angular velocity with respect to the sphere axis is ω(r) = u φ (r)/(r sin θ ), and if we define the angular velocity slip as ω = V /(R sin θ ) the result is Eq. (8).…”
Section: Slip Length In Curvilinear Coordinatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the fluid's angular velocity with respect to the sphere axis is ω(r) = u φ (r)/(r sin θ ), and if we define the angular velocity slip as ω = V /(R sin θ ) the result is Eq. (8).…”
Section: Slip Length In Curvilinear Coordinatesmentioning
confidence: 99%
“…This Navier slip BC has been widely used in gas dynamics [3] since the work of Maxwell [4], and in the last decade or two slip has been observed for liquid flows both in experiments (see the reviews in [1,[5][6][7][8]) and molecular dynamics computer simulations. The latter have indicated that the slip length in liquids depends critically on three factors: wettability, roughness and strain rate.…”
Section: Introductionmentioning
confidence: 99%
“…Columns 2 and 3 report the periodic cell dimensions, L x and L y respectively, column 4 the diameter D of the circular defect and column 5 the solid fraction smooth surfaces an increase in slip length with hydrophobicity was found for both MD and experiments, for a given contact angle θ the value of the experimental estimated L s is larger than MD results of about one order of magnitude. In particular in the case of the OTS coatings the most credited experimental data (obtained with different techniques (Bouzigues et al, 2008;Cottin-Bizonne et al, 2008;Li & Yoda, 2010)) indicates a slip length of ∼ 20nm while the MD value is in the range 0.5 − 1.5nm. Since the MD simulations were performed by different authors (Chinappi & Casciola, 2010;Chinappi et al, 2011;Huang et al, 2008;Sendner et al, 2009) using different force fields, computational codes and numerical set-ups, this discrepancy could hardly be ascribed to modeling inaccuracies affecting the MD simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their ability to form compact layers exposing the methyl (hydrophobic) group, OTS coatings represent a promising technology for surface functionalization. Several groups quantified the slip length L s of liquid water on smooth OTS coated surfaces (Bouzigues et al, 2008;Cottin-Bizonne et al, 2008;Li & Fig. 4.…”
Section: Slippage On Rough Surfaces: the Example Of Ots Coatingsmentioning
confidence: 99%
“…This originates from the importance of surface/ volume ratio inside micro-and nanofluidic devices, with dimensions possibly approaching that of the Navier slip length b. Detailed reviews on physical 153,154 and experimental 155,156 aspects of liquid slip have recently been published.…”
Section: Hydrodynamic Boundary Condition: Predictions and Measurementsmentioning
confidence: 99%